2020
DOI: 10.3390/nu12103129
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Inflammatory and Disease-Associated Plasma Proteins that Associate with Intake of Added Sugar and Sugar-Sweetened Beverages and Their Role in Type 2 Diabetes Risk

Abstract: It has been suggested that high intake of added sugar and sugar-sweetened beverages (SSBs) increase the level of circulating inflammatory proteins and that chronic inflammation plays a role in type 2 diabetes (T2D) development. We aim to examine how added sugar and SSB intake associate with 136 measured plasma proteins and C-reactive protein (CRP) in the Malmö Diet and Cancer–Cardiovascular Cohort (n = 4382), and examine if the identified added sugar- and SSB-associated proteins associate with T2D incidence. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…In an epidemiological study, no associations between sugar or sugar-sweetened beverages and CRP could be observed. The associations between some proteins involved in inflammatory response and sugar could not confirm causality, but could rather be a marker of high sugar intake and risk of type 2 diabetes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an epidemiological study, no associations between sugar or sugar-sweetened beverages and CRP could be observed. The associations between some proteins involved in inflammatory response and sugar could not confirm causality, but could rather be a marker of high sugar intake and risk of type 2 diabetes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…High dietary sugar intake has been proposed to increase subclinical inflammation, as shown by elevated C-reactive protein (CRP) in some previous studies [ 13 ]. Additionally, intake of added sugar and sugar-sweetened beverages is associated with increased expression of proteins involved in inflammatory response signaling [ 14 ]. Diets rich in sugar, starch and saturated fats could activate the innate immune system through increased production of pro-inflammatory cytokines [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, lack of these nutrients may also prompt the development and advancement of COVID-19 and its severe complications (46). Besides, a high intake of added sugar and sugar-sweetened beverages (SSBs) might elevate the level of circulating inflammatory proteins and chronic inflammation and may contribute to the onset of type 2 diabetes (47).…”
Section: Discussionmentioning
confidence: 99%
“…The higher luminal sugar concentrations, the more upregulation of the enzymatic and absorptive systems, with higher glucose absorption consequently ( 28 ). Accordingly, the increased sugar consumption has several effects on the homeostasis and thereby on health ( 60 ). Decreased intake of starch and sucrose does not only influence the GI symptoms ( 17 ), it also leads to weight reductions and a less risk of metabolic syndromes ( 61 ).…”
Section: Discussionmentioning
confidence: 99%